If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+8)=9(x+3
We move all terms to the left:
3(x+8)-(9(x+3)=0
We multiply parentheses
3x-(9(x+3)+24=0
| 7x+12=-7+3x | | | | |2x+3|-9=12 | | 1 x+6=16 | | 33=-8v+3(v+6) | | 5x+13=9x+5 | | -9p-8=-8p | | 3v=2v+36 | | | | 6x-1=3x-40 | | 4(1-5a)=-6(7a-8) | | | | | | | | | | | | | | 15x-42=143 | | 7(9+n)=84 | | 5+1/3x-9=-2 | | t=-4t^2+16t+48 | | 2x-5(x-3)=9x-10) | | -5x+8=−5x+8=-4x+9−4x+9 | | 15-42x=143 | | 3x-3=9-1x | | 4y+2(y-7)=130 | | (x)/(-5)=-8 | | 59=x-8 | | X+(2y-9)=24 | | F(1/3)=8-3x | | -16=n+7 | | 17=-3x+5x+1 |